Optimizing solar energy forecasting in Senegal: Sensitivity analysis of WRF-solar radiation schemes - Aissatou Ndiaye; Windmanagda Sawadogo; Jan Bliefernicht; Cheikh Dione; Mounkaila Saley Moussa; Laouali Dungall; Amadou Thierno Gaye; Harald Kunstmann (Theoretical and Applied Climatology, 2026)
Solar irradiance forecasting is essential in maximizing solar energy utilization and facilitating the shift towards an eco-friendly and sustainable energy future. However, accurate solar irradiance from numerical weather prediction remains challenging. This research evaluates the performance of state-of-the-art Weather Research and Forecasting tailored to the solar energy applications (WRF-Solar) at two operational solar plants in Senegal: Diass and Ten Merina. The experiments include different shortwave radiation schemes (Dudhia and RRTMG) with RRTMG coupled with dynamic aerosols. In addition, the impact of shallow convection on the different experiments is investigated. A total of six simulations is performed and assessed under various sky conditions using hourly GHI measurements for 2020. Results indicate that the RRTMG scheme coupled with aerosols outperforms other simulations, exhibiting a maximum correlation (R) of 0.85, skill score (SS) of 0.17, and the lowest RMSE value (160 W/m 2 ) and MAE (110 W/m 2 ). However, WRF-Solar exhibits poor performance across all experiments (RMSE = 386 W/m², R = 0.55, SS = -1.48) under cloudy skies. The influence of the shallow convection scheme in the WRF-Solar model on GHI estimation was found to be limited under different atmospheric conditions at both sites. These findings offer valuable insights that can enhance solar energy forecasting accuracy and support reliable solar power generation and renewable energy optimization, benefiting energy providers, policymakers, and communities in Senegal.

Agriculture in the face of climate change and socio-economic prospects to 2050 in Senegal - Touré Abdou Kader; LY Ahmadou; Diakhaté Moussa; Fall Cheikh M. Noreyni; Camara Ibrahima; Ndiaye Ousmane; Dièye Bounama; Diop Mbaye; Gaye Amadou Thierno (Mitigation and Adaptation Strategies for Global Change, 2025)

Upcycling Guiera Senegalensis waste into biochar for sustainable amoxicillin removal from water - Cheikh Gaye; Jorge Rodríguez-Chueca; Alba Ortíz Fuduo; Modou Fall; Patricia García-Muñoz (Journal of Water Process Engineering, 2025)

From vulnerability to viability: A situational analysis of small-scale fisheries in Asia and Africa - Ana Carolina Esteves Dias; Derek Armitage; Prateep Kumar Nayak; Shehu Latunji Akintola; Evans Kwasi Arizi; Ratana Chuenpagdee; Basanta Kumar Das; Sabiha Ahmed Diba; Raktima Ghosh; Moenieba Isaacs; Gazi Md Nurul Islam; Alioune Kane; et al. (Marine Policy, 2023)

Correction to: Forest Genetics Research in the Mediterranean Basin: Bibliometric Analysis, Knowledge Gaps, and Perspectives - Bruno Fady; Edoardo Esposito; Khaled Abulaila; Jelena M. Aleksic; Ricardo Alia; Paraskevi Alizoti; Ecaterina-Nicoleta Apostol; Phil Aravanopoulos; Dalibor Ballian; Magda Bou Dagher Kharrat; Isabel Carrasquinho; Marwan Cheikh Albassatneh; et al. (Current Forestry Reports, 2022)

Forest Genetics Research in the Mediterranean Basin: Bibliometric Analysis, Knowledge Gaps, and Perspectives - Bruno Fady; Edoardo Esposito; Khaled Abulaila; Jelena M. Aleksic; Ricardo Alia; Paraskevi Alizoti; Ecaterina-Nicoleta Apostol; Phil Aravanopoulos; Dalibor Ballian; Magda Bou Dagher Kharrat; Isabel Carrasquinho; Marwan Cheikh Albassatneh; et al. (Current Forestry Reports, 2022)
Purpose of Review Recognizing that in the context of global change, tree genetic diversity represents a crucial resource for future forest adaptation, we review and highlight the major forest genetics research achievements of the past decades in biodiversity-rich countries of the Mediterranean region. For this, we conducted a bibliometric analysis of the scientific literature spanning the past thirty years (1991–2020). Putting together the representative regionwide expertise of our co-authorship, we propose research perspectives for the next decade. Recent Findings Forest genetics research in Mediterranean countries is organized into three different scientific domains of unequal importance. The domain “Population diversity and Differentiation” related to over 62% of all publications of the period, the domain “Environmental conditions, growth and stress response” to almost 23%, and the domain “Phylogeography” to almost 15%. Citation rate was trending the opposite way, indicating a strong and sustained interest in phylogeography and a rising interest for genetics research related to climate change and drought resistance. The share of publications from Asia and Africa to the total within the Mediterranean increased significantly during the 30-year period analyzed, reaching just below 30% during the last decade. Summary Describing poorly known species and populations, including marginal populations, using the full potential of genomic methods, testing adaptation in common gardens, and modeling adaptive capacity to build reliable scenarios for forest management remain strategic research priorities. Delineating areas of high and low genetic diversity, for conservation and restoration, respectively, is needed. Joining forces between forest management and forest research, sharing data, experience, and knowledge within and among countries will have to progress significantly, e.g., to assess the potential of Mediterranean genetic resources as assisted migration material worldwide. Introductory quote: Let us collect with care the facts we can observe, let us consult experience wherever we can, and when this experience is inaccessible to us, let us assemble all the inductions which observation of facts analogous to those which escape us can furnish and let us assert nothing categorically; in this way, we shall be able little by little to discover the causes of a multitude of natural phenomena, and, perhaps, even of phenomena which seem the most incomprehensible... J.B. de Lamarck (Philosophie zoologique, 1809), cited by O. L anglet (1971).

Preface: Groundwater in Sub-Saharan Africa - Yongxin Xu; Paul Seward; Cheikh Gaye; Lixiang Lin; Daniel O. Olago (Hydrogeology Journal, 2019)

Tracing natural groundwater recharge to the Thiaroye aquifer of Dakar, Senegal - Seynabou C. Faye; M. L. Diongue; Abdoulaye Pouye; Cheikh B. Gaye; Yves Travi; Stefan Wohnlich; Serigne Faye; Richard G. Taylor (Hydrogeology Journal, 2019)

Review: Challenges and opportunities for sustainable groundwater management in Africa - Cheikh B. Gaye; Callist Tindimugaya (Hydrogeology Journal, 2019)

Assessment of the impacts of climate variability on total water storage across Africa: implications for groundwater resources management - Tales Carvalho Resende; Laurent Longuevergne; Jason J. Gurdak; Marc Leblanc; Guillaume Favreau; Nienke Ansems; Jac Van der Gun; Cheikh B. Gaye; Alice Aureli (Hydrogeology Journal, 2019)

Do Sardinella aurita spawning seasons match local retention patterns in the Senegalese–Mauritanian upwelling region? - Baye Cheikh Mbaye; Timothée Brochier; Vincent Echevin; Alban Lazar; Marina Lévy; Evan Mason; Amadou Thierno Gaye; Eric Machu (Fisheries Oceanography, 2015)
Sardinella aurit a is the most abundant small pelagic fish in the Senegalese–Mauritanian region. The success of its reproduction crucially depends on the local circulation as this determines whether larvae reach coastal nursery areas favorable to their survival or are dispersed into the open ocean. As a first step towards evaluating sardinella vulnerability to climate‐driven hydrodynamical changes, this study aims at underpinning how transport pathways drive optimal spatial and seasonal patterns for sardinella reproduction. We have used two estimates of the Senegalese–Mauritanian coastal seasonal circulation simulated by two hydrodynamical model configurations that differ in their forcing and topography. Nursery areas are determined by evaluating coastal retention with a Lagrangian individual‐based model that accounts for processes such as diel vertical migration and mortality as a result of lethal temperature exposure. Our results suggest that the shelf zones located at the Arguin Bank (19.5°N–21°N) and south of Senegal (12°N–14.75°N) are highly retentive. We find maximum retention rates in July–August and November–December over the Arguin Bank; from February–July and November–December over the southern Senegalese shelf; and lower retention rates over the central region (14.75°N–19.5°N) that are locally maximum in June–July when the upwelling weakens. These retention areas and their seasonality are in agreement with previously reported spawning patterns, suggesting that the Sardinella aurita spawning strategy may result from a trade‐off between retention patterns associated with the seasonal circulation and food availability. Exposure to lethal temperatures, although not well studied, could be a further limiting factor for spawning. The Lagrangian analysis reveals important connectivity between sub‐regions within and south of the system and hence underlines the importance for joint management of the S ardinella aurita stock.

Cryptococcal Meningitis in Senegal: Epidemiology, Laboratory Findings, Therapeutic and Outcome of Cases Diagnosed from 2004 to 2011 - Doudou Sow; Roger Clément Tine; Khadime Sylla; Mansata Djiba; Cheikh Tidiane Ndour; Thérèse Dieng; Jean Louis Ndiaye; Babacar Faye; Daouda Ndiaye; Oumar Gaye; Yémou Dieng (Mycopathologia, 2013)

Water quality decline in coastal aquifers under anthropic pressure: the case of a suburban area of Dakar (Senegal) - Viviana Re; Seynabou Cissé Faye; Abdoulaye Faye; Serigne Faye; Cheikh Becaye Gaye; Elisa Sacchi; Gian Maria Zuppi (Environmental Monitoring and Assessment, 2011)

Fluorimetric Determination of Histamine in Fish Using Micellar Media and Fluorescamine as Labelling Reagent - Rabani Adamou; Atanasse Coly; Stephy Edgar Douabalé; Med Lemine Ould Cheikh Ould Saleck; Mame Diabou Gaye-Seye; Alphonse Tine (Journal of Fluorescence, 2005)

Editor’s Message Isotope techniques for monitoring groundwater salinization - Cheikh B. Gaye (Hydrogeology Journal, 2001)